Online Medical Education in Nepal: Barking a Wrong Tree - Nepal, Binu; Atreya, Alok (Journal of Lumbini Medical College, 2020)
To combat the global pandemic of Covid-19, the Government of Nepal declared a country wide lockdown on 24 March, 2020. The lockdown affected all the institutions, medical schools being no exception. To keep in pace with the academic calendar, most of the universities instructed their affiliated medical schools to start online classes for medical undergraduates. Kathmandu University which affiliates ten medical schools under its umbrella circulated a notice to start online classes. To facilitate this, the most important requisite is internet connection. A working device in the form of a laptop, desktop, or smartphone is needed to log in through the internet. After the lockdown, when all the medical schools closed, the students went home. We should not forget the fact that many students are from rural locality with no access to the internet at their home. The mobile internet data is costly and more data is consumed during video conferencing in online classes. The geographical remoteness further hinders the network coverage across the country.